The EFFECTIVENESS OF USE OF POSTERS AS A HEALTH PROMOTION MEDIA ON SELF CARE MANAGEMENT KNOWLEGDE OF DEGENERATIVE JOINT DISEASE IN ELDERLY: EFEKTIFITAS PENGGUNAAN POSTER SEBAGAI MEDIA PROMOSI KESEHATAN TERHADAP PENGETAHUAN SELF CARE MANAGEMENT PENYAKIT DEGENERATIF SENDI INSAN LANJUT USIA - Dwi Setiyawati; Hendrawan, Arief (UPT PPM Sekolah Tinggi Ilmu Kesehatan Al Irsyad Al Islamiyyah Cilacap, 2021)
The COVID-19 pandemic has created anxiety and concern for the public to visit health facilities. Efforts are needed to continue to provide knowledge to the public about physical health and degenerative disease, especially at this time. One of the promotive effort to increase public health understanding is the use of health promotion media. The use of health promotion media is very effective to increase the level of public konwlegde. This studi aims to ditermine the effectiveness of using posters as a medium for health promotion on knowlegde of self care management of degenerative diseases of the elderly. The research method that will be applied is analytical description research with purposive sampling technique. The research design is one group pretest-posttes. The study was conducted from March to July 2020 on 21 respondents from the Nurul Huda Taqlim Assembly in Menganti Village, Kesugihan District, Cilacap Regency. The data analysis technique used paired sample t test. The result showed that the effectiveness of the use of posters as a medoum for health promotion on self care managemen knowlegde of degenerative joint disease in elderly people (p=0,001)